Green spot in ‘WA 38’: Growth dynamics, vascular integrity and architecture, and a hypothetical mechanism - Bruno Carra; Sara Serra; Moritz Knoche; David Rudell; Stefano Musacchi (PLoS ONE, 2026)
‘WA 38’ is a cross of ‘Enterprise’ and ‘Honeycrisp’. It is susceptible to the surface disorder known as green spot (GS), which reduces its marketability. This study aimed to characterize fruit growth in ‘WA 38’, ‘Enterprise’, and ‘Honeycrisp’ and explore potential links to vascular integrity. Among the three cultivars, ‘WA 38’ exhibited the most rapid fruit growth, followed by ‘Enterprise’ and ‘Honeycrisp’. While fruit diameter was similar across cultivars, ‘WA 38’ apples were significantly longer. Allometric analysis revealed hyperallometric growth in the height of the calyx lobes and pedicel end region relative to diameter in all cultivars. Conversely, core height growth was hypoallometric. ‘WA 38’ showed faster calyx lobe elongation than either parent cultivar. However, in the pedicel end region, ‘Honeycrisp’ exhibited faster growth than ‘WA 38’. The positions of the vascular bundles were unusual across the three cultivars. Petal bundles were more peripheral than sepal bundles in ‘WA 38’, followed by ‘Enterprise’ and ‘Honeycrisp’. Acid fuchsin feeding pedicels of immature ‘WA 38’ fruit stained sepal and petal bundles and a dense network of minor veins. In mature fruit, staining was limited to petal and sepal bundles near the seed cavity. More petal bundles were stained in immature fruit than mature fruit, while sepal bundle staining remained constant. Notably, rupture of petal bundles occurred near the seed cavity. Green spot disorder did not consistently affect the calcium-to-dry-mass ratio. The xylem of ‘WA 38’ becomes dysfunctional, probably because of hyperallometric growth in height at the pedicel end and the unusual peripheral position of petal bundles. Although the total Ca/dry mass ratio of ‘WA 38’ appears sufficiently high, imbalances will likely arise between different Ca pools within the fruit.